Melatonin feeding changed the microbial diversity and metabolism of the broiler cecum - Zhen, Li; Huang, Yi; Bi, Xuewen; Gao, Anyu; Peng, Linlin; Chen, Yong (Frontiers in Microbiology, 2024)
To study the effect of melatonin supplementation on the gut microbes of broilers, 160 healthy 3week-old Ross 308 broilers with similar body weights were selected and randomly divided into four groups (M0, M20, M40, and M80) supplemented with 0, 20, 40, or 80 mg/kg melatonin. The results showed that the abundance-based coverage estimator (ACE) index of cecum microorganisms was significantly lower in the M80 group. The dominant phyla of intestinal contents in the M0, M20, M40, and M80 groups were Bacteroidetes and Firmicutes. The M40 group showed an increase in the relative abundance of Bacteroidetes spp. in the intestine, while the relative abundance of Ruminococcus spp. in the intestine of the M20, M40, and M80 groups was significantly greater than that of the M0 group. Kyoto Encyclopedia of Genes and Genomes (KEGG) functional analyses revealed that the supplementation of melatonin increases the expression of genes related to cellular processes (cell motility, cell growth and death, cellular community-eukaryotes), environmental information processing (membrane transport, signal transduction) and genetic information processing (transport, transcription), and Cluster of Orthologous Groups of proteins (COG) functional analyses revealed that the supplementation of melatonin resulted in a significant increase in Cellular Processes and Signaling (cell motility, signal transduction mechanisms, intracellular trafficking, secretion, and vesicular transport), Information Storage and Processing (RNA processing and modification, chromatin structure and dynamics, translation, ribosomal structure, and biogenesis), Metabolism (energy production and conversion, lipid transportation and metabolism, inorganic ion transport and metabolism, secondary metabolite biosynthesis, transport, and catabolism), and Poorly Characterized (general function prediction only). In summary, supplementation of feed with melatonin can increase the diversity of intestinal microorganisms and the relative abundance of Bacteroides and Firmicutes in the cecum, improve digestive ability and nutrient absorption ability, and positively regulate the metabolic ability of broilers.